BPJS Employment Communication Strategy in Improving Informal Sector Workers' Awareness of the Employment Social Security Program - Al-Ghifari, Maulana; Gurning, Sarah Louis Angelica; Nababan, Desika; Siahaan , Febby (PT. Anagata Sembagi Education, 2026)
The low participation of informal sector workers or Non-Wage Recipients (BPU) in employment social security is a national challenge, primarily due to a lack of awareness and cost perception barriers. This study aims to describe BPJS Employment's communication strategy in acquiring BPU participants through a comprehensive review of previous literature. The method used is qualitative with a library research approach. Data collection was carried out by reviewing scientific journals, books, and performance reports for the 2020–2025 period. The review results showed that the most effective communication strategy is the personal selling approach through Perisai Agents who apply the AIDDA (Attention, Interest, Desire, Decision, Action) model. Perisai Agents act as communication bridges capable of overcoming trust issues and low digital literacy among informal workers. These findings recommend the need to strengthen agents' persuasive communication capacity and integrate digital communication channels for membership sustainability.